Can organisation capital improve corporate performance through direct path or mediating effect surveillance of board function: evidence from Taiwan? - Wang, Mu-Shun; Lu, Shih-Tong (Technological and Economic Development of Economy, 2017)
This paper examines whether board function is associated with improved corporate performance. Path analysis is used to investigate the direct and indirect links between four performance variables and organization capital. A hypothesis is developed based upon the incorporation of knowledge-based resources. The idea is that the board of directors has monitoring and consultation functions, propelling organizational development. We use panel data with random effects for 1,355 firms listed on the Taiwan Stock Exchange from 2001 to 2012. The two-stage leastsquares method is used to explore the mediating effect among board function, organization capital and corporate performance. Both an aggregated model and the EP model are investigated specifying both a direct link and a mediated link with organization capital. It is concluded that the governance effect has a direct influence in the relationship between board function and corporate governance, and that organization capital is significantly associated with the performance variables. In terms of the counselling function of the board, inside directors are significantly related to dynamic capacity, which improves corporate performance for the long run. First published online: 03 Nov 2015